Can the KG1 cell line be used as a model of dendritic cells and discriminate the sensitising potential of chemicals?. Issue 1 (19th November 2015) - Curtis, Angela; Morton, Jackie; Fraser, Susan; Harding, Anne-Helen; Prideaux, Brendan; Clench, Malcom; Warren, Nicholas D.; Evans, Gareth S.
Abstract The KG1 myeloid leukaemia was used as source of dendritic cells (DC) to discriminate between respiratory and contact sensitising chemicals. A cocktail of cytokines was used to differentiate KG1 to dendritic like cells (termed dKG1) and the effects of nine chemicals (respiratory and contact sensitisers) and an irritant control on surface marker expression, 'antigen presenting' function and cytokine expression investigated. The stability of these chemicals when dissolved was characterised using MALDI ToF MS. A Hill plot model was used with the cellular viability data to quantify the lethal dose 50% (LD50) and a maximum sub toxic concentration of each chemical defined. Cytokine expression by the treated dKG1 was quantified using multiplex immunobead analysis. Whilst dKG1 cells were morphologically similar to DCs, expression of specific surface markers was not typical for DCs derived from healthy precursor cells. When the chemicals were applied at defined sub toxic doses no effects on dKG1 phenotype, function, or cytokine expression, attributable to the sensitisation properties were discriminated. However, dKG1 cells were much more sensitive to the toxic effects of these chemicals compared to the parent KG1 cells. Only 4 of the 9 chemicals tested were stable when dissolved indicating that the effect of sensitising chemicals on antigen presenting cells may be related to species other than the parent compound.